Reversible Ultra‐Slow Crystal Growth of Mixed Lead Bismuth Perovskite Nanocrystals: The Presence of Dynamic Capping. Issue 7 (22nd January 2020) - Chatterjee, Shovon; Dey, Pritam; Das, Nilimesh; Tiwari, Khushubo; Maiti, Tanmoy; Sen, Pratik
Abstract: An ultra‐slow crystal growth over a period of 24 h of a newly synthesized CH3 NH3 Pb1/2 Bi1/3 I3 perovskite (MPBI) nanocrystal in non‐polar toluene medium is reported here. From several spectroscopic techniques as well as from TEM analysis we found that the size of nanocrystals changes continuously with time, in spite of being capped by the ligands. Using a single molecular spectroscopic technique, we also found that this size change is not due to the stacking of nanocrystals but due to crystal growth. The notable temperature dependence and reversible nature of the nanocrystals growth is explained by the dynamic nature of the capping. The observed temperature‐dependent ultra‐slow growth is believed to be a pragmatic step towards controlling the size of perovskite NC in a systematic manner. Abstract : An ultra‐slow crystal growth process of a newly synthesized perovskite nanocrystal until 24 hours in a normal antisolvent medium is reported here (see scheme). The crystal growth is observed through successive spectral evolutions in a macroscopic as well as in a microscopic regime. Through the reversibility in temperature dependence we have proved that the crystal growth is mediated by the dynamic capping.